FORMULATION AND TESTING OF ANTIOXIDANT ACTIVITY COMBINATION OF CALENDULA OIL AND SWEET ORANGE OIL WITH DPPH METHOD - Deni Firmansyah; Sulistiorini Indriaty; Nina Karlina; Eka Mardiyani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Indonesia has many natural ingredients that can be used as primary ingredients for medicines with antioxidant effects. Calendula oil and sweet orange oil have the potential to be antioxidants. This study aimed to determine the stability of cream preparations based on stability test parameters and to determine antioxidant activity using the DPPH method. This study was conducted because the combination of calendula oil and sweet orange oil was tested for antioxidant activity and then formulated in cream dosage forms with ratio of 1:1, 1:2, and 2:1. Antioxidant activity tests were carried out using a combination of calendula oil and sweet orange oil and a cream preparation of a combination of calendula oil and sweet orange oil, which was tested for stability using the cycling test method. Based on the results of the study, the combination of calendula oil and sweet orange oil in a ratio of 1:1 and 1:2 had weak antioxidant activity, as can be seen from the IC50 value of 170.02 ppm, 150.43 ppm, whereas in a 2:1 ratio, it had moderate antioxidant activity because the IC50 value was 143.89 ppm. In the combination cream preparations of calendula oil and sweet orange oil, ratios of 1:1, 1:2, and 2:1 had weak antioxidant activity. It can be seen from the IC50 value of each preparation, which was 188.85 ppm, 170.01 ppm, and 189.61 ppm. Keywords: Calendula Oil, Sweet Orange Oil, Antioxidant, Cream, DPPH